2021
DOI: 10.1155/2021/8924087
|View full text |Cite
|
Sign up to set email alerts
|

Diversified Crop Rotation: An Approach for Sustainable Agriculture Production

Abstract: Diversified crop rotation (DCR) improves the efficiency of farming systems all over the world. It has the potentiality to improve soil condition and boost system productivity. Improved soil attributes such as increased soil water uptake and storage, and a greater number of beneficial soil organisms, may improve yield tolerance to drought and other hard growing conditions in a variety of crop rotations. Crop rotations with a variety of crops benefit the farmers,reduce production risk and uncertainty, and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 89 publications
1
24
0
Order By: Relevance
“…Third, based on our data, combined practices, crop rotation, embedding natural habitat, and agroforestry, each lead to significantly higher profits in terms of net income, or benefit-cost ratio in the case of agroforestry. Previous reviews have similarly suggested that crop rotation usually results in higher income and fewer production risks, particularly for low-income smallholder farmers (Feliciano, 2019;Shah et al, 2021). However, the adoption of diversified rotation systems may be negatively influenced by the higher investment (e.g., inputs, machinery, labour) needed to integrate and manage extra crops compared to simpler rotations (Feliciano, 2019), which may explain the higher costs for crop rotations found in our study.…”
Section: Diversified Farming Systems Make Economic Sensementioning
confidence: 54%
“…Third, based on our data, combined practices, crop rotation, embedding natural habitat, and agroforestry, each lead to significantly higher profits in terms of net income, or benefit-cost ratio in the case of agroforestry. Previous reviews have similarly suggested that crop rotation usually results in higher income and fewer production risks, particularly for low-income smallholder farmers (Feliciano, 2019;Shah et al, 2021). However, the adoption of diversified rotation systems may be negatively influenced by the higher investment (e.g., inputs, machinery, labour) needed to integrate and manage extra crops compared to simpler rotations (Feliciano, 2019), which may explain the higher costs for crop rotations found in our study.…”
Section: Diversified Farming Systems Make Economic Sensementioning
confidence: 54%
“…The C-W-B-P-C rotational sequence also provided distinct advantages with respect to the management of common annual weeds in dryland rotations. For example, planting canola in year 1 of a rotation would enable the targeted control of gramineous weeds, including herbicide-resistant annual ryegrass, using multiple selective preemergent herbicides [33]. In low input, no tillage, or conservation tillage systems, a subsequent competitive wheat or barley crop following canola can typically provide fierce weed competition due to early vigour traits expressed by these cereals [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, planting canola in year 1 of a rotation would enable the targeted control of gramineous weeds, including herbicide-resistant annual ryegrass, using multiple selective preemergent herbicides [33]. In low input, no tillage, or conservation tillage systems, a subsequent competitive wheat or barley crop following canola can typically provide fierce weed competition due to early vigour traits expressed by these cereals [33]. Pulse and other legumes that follow cereal crops benefit from a depleted weed seedbank and can generally fix substantial atmospheric nitrogen, further benefiting the subsequent canola crop and its related yields [34].…”
Section: Discussionmentioning
confidence: 99%
“…It helps in understanding the importance of the disease-free crop and to get the maximum output. In similar objectives, the crop rotation policy also helps [14]. e benefit of crop rotation is that the soil is not getting exhausted with similar types of nutrients in the soil, and it helps to maintain a good balance of the different nutrients in the soil.…”
Section: Related Workmentioning
confidence: 99%